(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In today world importance of exchange of data over internet and other media type is eminent; the search for best data protection against security attacks and a method to timely deliver the data without much delay is the matter of discussion among security related communities. Cryptography is one such method that provides the security mechanism in timely driven fashion. Cryptography is usually referred to as "the study of secret", which is most attached to the definition of encryption. The two main characteristics that identify and differentiate encryption algorithm from another are their capability to secure the protected data against attacks and their speed and effectiveness in securing the data. This paper provides a comparative study between four such widely used encryption algorithms DES, of DES, 3DES, AES and RSA on the basis of their ability to secure and protect data against attacks and speed of encryption and decryption.